The Impact of Crisis Response Strategies on Consumer Attitudes and Perceptions towards Halal Brands - Imran, Hina (2016)
Purpose – The purpose of the present study is to understand the impact of varying crisis response strategies on consumers’ attitudes and perceptions when used in a Halal crisis situation and also to study how different levels of consumer skepticism determines the magnitude of impact on consumer perceptions. Methodology – Data was collected from 171 Malaysian residents, particularly Muslims only, using snowball and convenience sampling. The data was later analyzed using IBM SPSS Statistics 20. Findings – The results show that while there exists a significant relation between high and low skepticism consumers towards only the accommodative response strategy while no significant relation exists between them, towards the defensive strategy. However, the high skepticism consumer groups show a more positive response towards the defensive strategy than the accommodative. Practical implications – Halal crisis managers should understand the significance of consumers with high levels of skepticism. It is crucial to keep them satisfied and to use Halal practices and crisis communications such that they do not become skeptical about their brand in the long run. A consumer with high level of religiosity may go into the search of extra information from several sources before it can make judgment regarding a Halal brand. Thus, to satisfy such consumers, Halal crisis managers really need to devise effective crisis response strategies that would make them evaluate their brand positively. Originality/Value – Despite there being a number of studies carried out in the field of crisis communications, barely any research exists on the use of crisis response strategies in Halal crisis situations and how consumer skepticism influences post-crisis consumer attitudes towards the Halal brands. The empirical evidence of this study will contribute to the literature on crisis communications.